High molecular weight hyaluronic acid for treating corneal nerve injury or loss - MULLER-LIERHEIM WOLFGANG GEORG KONRAD; VAN SETTEN GISBERT-BOTHO (2023)
The present invention relates to a method for treating nerve injury or loss (corneal nerve injury or loss) in the cornea of an eye of a human or non-human animal subject, comprising topically applying to the ocular surface of the eye a fluid comprising high molecular weight hyaluronic acid (HMWHA) wherein the hyaluronic acid has an intrinsic viscosity of at least 2.5 m3/kg. 本发明涉及一种用于治疗人或非人动物受试者的眼睛的角膜中的神经损伤或损失(角膜神经损伤或损失)的方法，包括将包含高分子量透明质酸(HMWHA)的流体局部施用到眼睛的眼表面，其中所述透明质酸具有至少2.5m3/kg的特性粘度。